(untitled) (Teaching and Learning Inquiry, 2022)
This article presents findings from a small-scale qualitative study of student perceptions of a High Achievers’ Recognition Scheme in a faculty within a UK university. This scheme is unusual in UK higher education in that it provides tailored support and development for students who have been identified as high-achievers. The findings suggest students valued both the recognition and developmental aspects of the scheme and their perceptions of the benefits aligned with the scheme’s aims: enhanced personal and professional development, improved engagement, and raised aspirations. Social and individual factors were perceived to enable high-achievement, whilst some operational factors could hinder engagement with the scheme. The findings are relevant to wider understandings of approaches to support high-achieving students; an area where, currently, there is little published research from the UK. We conclude with reflections on possible ways to build support for high-achieving students through focusing on identity, agency, and community.